Financial Analysis with Microsoft Excel, 9th Edition - Timothy R. Mayes (Cengage Learning, 2020)
Equip your students with the skills and knowledge to solve real-world financial problems as Mayes' FINANCIAL ANALYSIS WITH MICROSOFT® EXCEL®, 9E combines the power of Excel® with a solid foundation in corporate finance. This edition provides a new focus on time series forecasting and Get & Transform tools (formerly Power Query). Comprehensive coverage addresses the corporate finance topics and tool most important to today's employers, including financial statements, cash budgets, the Security Market Security Line, pro forma financial statements, cost of capital, Visual Basic Applications (VBA) programming and pivot tables. A reader-friendly, self-directed learning approach and numerous study tools make this resource ideal for learners of all levels. This edition begins with the basics before quickly moving into more advanced Excel® features. The easy-to-understand presentation helps students solidify spreadsheet skills while strengthening an understanding of contemporary corporate finance.